Формування податкової культури в Україні та аналіз її складових частин - Ручкіна, В.Н. (Економіка промисловості, 2013)
Визначено чинники формування та розвитку податкової культури в Україні. Проведено аналіз її складових частин. Проаналізовано податкову культуру як складову податкового потенціалу держави. Визначено напрями розвитку податкової культури в Україні. Досліджено роль податкової культури в умовах стимулювання економічного розвитку в Україні.
Ключові слова: податкова культура, податковий потенціал, інституційне середовище, податкова система. Определены факторы формирования и развития налоговой культуры в Украине. Проведен анализ ее составляющих частей. Проанализирована налоговая культура как составляющая налогового потенциала государства. Определены направления развития налоговой культуры в Украине. Исследована роль налоговой культуры в условиях стимулирования экономического развития в Украине.
Ключевые слова: налоговая культура, налоговый потенциал, институциональная среда, налоговая система. Formation of the institutional surrounding and reducing of parallel uncontrolled financial flows in economy determine the role of tax culture in the institutional aspect of the tax system of Ukraine.
In economic literature tax culture is considered in the context of cooperation between state tax regulator and the taxpayer. It is reasonable to study tax culture in the context of institutional theory. The study is an analysis of tax culture in the institutional aspect of the tax system of Ukraine.
The article analyzes the legal, economic, and social factors of parallel (shadow) economy as a part of the tax unrealized potential. Ukraine's tax system must meet global standards. The formation and development of tax culture is one of the directions of reforming the tax system. Institutional environment of tax system and the problems of formation and development of tax culture in Ukraine are identified and analyzed.
The institutional environment of the state tax system includes a set of legal, economic, and cultural institutions. Legislative institutions shape the regulatory framework in the tax area. The economic component of the institutional environment stimulates the activity of entities using the tools of tax policy. The tax cultural component includes tax awareness, professional identity, and ethics of doing business. Tax culture in the institutional aspect can be defined as the beliefs, values, knowledge, which provide for the timely payment of taxes and mandatory contributions under the terms of the current legislation of the state.
Formation and development of tax culture is implemented through formal and informal institutions. Formal institutions create a legislative platform; informal institutions are the platform beliefs, values, and knowledge. One of the main problems of the formation and development of tax culture is rather low opinion of the population on the need to pay taxes.
Keywords: tax system, potential of taxation, institutional surrounding, tax culture.